Pendampingan Penerbitan Buletin Atsar melalui Pelatihan Jurnalistik bagi Siswa MA Salafiyah Simbangkulon Kabupaten Pekalongan - Dimas Prasetya; Mukoyimah Mukoyimah; Ryan Marina; Arditya Prayogi; Hanif Ardiansyah (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
School bulletins are a learning medium that can support the development of students' literacy and writing skills. However, managing school bulletins often faces challenges in the form of limited student understanding of journalistic fundamentals and news writing techniques. This situation was also found among the Atsar Bulletin administrators at MA Salafiyah Simbangkulon, Pekalongan Regency. This community service activity aimed to improve students' journalistic understanding and skills through mentoring the publication of bulletins based on journalism training. The activity was held on February 7, 2025, in a classroom at MAS Simbang Kulon, involving 24 Atsar Bulletin student administrators. The method used was a participatory approach through four stages: planning (pre-activity), training implementation, writing practice, and evaluation. The material covered journalistic fundamentals, news types, news structure, and news writing techniques. The results of the activity showed an increase in participants' understanding of journalistic fundamentals, their ability to differentiate news types, their understanding of journalistic codes of ethics, and their skills in composing news headlines and leads. This activity demonstrates that practice-based journalism training is effective in supporting the development of students' literacy and writing skills.